Updating of sewage - purification facilities of electroplating enterprises with counterflow ion-exchange filters; IOP Conference Series: Materials Science and Engineering; Vol. 91: VI International Scientific Practical Conference on Innovative Technologies and Economics in Engineering, Yurga, Russia, 21-23 May 2015 - Torosyan V. F. Vera Fedorovna; Torosyan E. S. Elena Samvelovna; Sorokin P. D.; Telitsyn A. A. (Environmental protection, industrial labor safety, 2015)
Title screen